Ectopic intracranial retinoblastoma in a 3.5-month-old infant without eye involvement and without evidence of heritability - Römer, Tristan; Sturm, Dominik; Deimling, Andreas von (Pediatric blood & cancer, 2019)
Heritable retinoblastoma can rarely be associated with a midline intracranial neuroblastic tumor, referred to as trilateral retinoblastoma. We present an unusual midline brain tumor in an infant that was identified as ectopic retinoblastoma by histopathology, DNA methylation analysis, and molecular genetic detection of biallelic somatic inactivation of the RB1 gene. There was no ocular involvement, and germline mutation was excluded. In this nonresectable tumor, treatment with systemic chemotherapy including high-dose therapy with autologous stem cell transplantation, but without definite local therapy, resulted in long-lasting tumor control.
Gesehen am 04.04.2019